Effects of feeding different levels of low crude protein diets with different levels of amino acids supplementation on layer hen performance - Mohan, Tenesa; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi; Mohamad, Rosfarizan; Abdul Rahim, Raha (Universiti Putra Malaysia Press, 2016)
The use of synthetic amino acids (methionine, lysine, threonine) makes the formulation of diets with minimum levels of crude protein possible. The objective of this study was to determine the effects of low crude protein diet with amino acids supplementation on the performance, egg production, small intestine villus height and faecal LAB and ENT count in laying hens. A total of 144 16-week old layer hens of Hisex brown were assigned to four dietary treatments: 17.5% CP (control); (ii) 17.5% CP; (iii) 17% CP; and (iv) 16.5% CP supplemented with amino acids. Treatment group supplemented 17% CP was significantly higher (P<0.05) in egg production than other groups. Nonetheless, there were no significant differences (P>0.05) in egg quality. Results showed significant differences (P<0.05) in both villi height and crypt depth in duodenum, jejunum and ileum. The treatment supplemented with 17% CP showed a significant reduction (P<0.05) in faecal pH compared to the other groups. There was a significant different (P<0.05) in LAB and ENT count and LAB/ENT ratio among the dietary treatments. In conclusion, 17% CP treatment supplemented with amino acids demonstrated the best effects in improving the hens' egg production, small intestine villus height and even promoting beneficial effects of faecal microflora.